The Black Death in Egypt and England: A Comparative Study By Stuart J. Borsch (Austin: University of Texas Press, 2005. 195 pages.) (American Journal of Islam and Society, 2007)
In this cross-regional comparative study, Stuart Borsch marshals medievaleconomic data to address why, following the Black Death, “Egypt’s centralizedand urban landholding system was unable to adapt to massive depopulation,while England’s localized and rural landholding system had fullyrecovered by the year 1500” (dust jacket). After making a quick dispatch ofantiquated theories and flawed research, he introduces new findings onmedieval Egypt’s sharp financial downturn in contrast to England’s economicstabilization and upswing.The author points out that both states were centralized monarchies withsimilar population levels and agrarian-based economies overseen by “bigstick” aristocracies. Egypt had a modicum of arable land along the Nile;England had large areas of pastoral land and far more arable soil (pp. 16-17).In addition, Egypt’s nonhereditary ruling Mamluk elite, imported Caucasianand Central Asian slave children (some of whom actually ruled), becameiron-handed absentee landholders: “A vast gulf separated the Mamlukwarrior-landholder from the Egyptian peasant. A barracks-trained TurkishorCircassian-speaking Mamluk and a village peasant were probably as ...